Conflict dynamics among former elites of the Free Aceh Movement after the Helsinki agreement: A case study of regional head elections in Aceh - Sahruddin, Sahruddin; Rahmatunnisa, Mudiyati; Djuyandi, Yusa; Muradi, Muradi (Research Journal in Advanced Humanities, 2024)
This research investigates the conflict dynamics between former Free Aceh Movement (GAM) elites in the context of post-MoU Helsinki local elections in Aceh. The focus is to provide a comprehensive view of Aceh’s post-peace political dynamics and its contribution to developing policies to strengthen political stability and reconciliation in the region. The research uses an exploratory case study approach with primary data from in-depth interviews and participatory observation of former GAM elites, local politicians, conflict observers, and community leaders. Secondary data sources included Aceh’s historical literature, treaty documents, and academic journal articles. Analysis was conducted inductively to conclude. The Helsinki Peace Agreement was essential in ending the armed conflict between GAM and the Indonesian government. Besides mandating the demobilization and reintegration of former GAM members through the Aceh Transitional Committee (KPA), the agreement also paved the way for GAM’s transformation into a legitimate political force with the formation of Partai Aceh. The results also show that GAM’s transformation has had a significant positive impact on Aceh’s political stability and Aceh’s integration into the framework of the unitary state of the Republic of Indonesia. However, challenges such as internal dissent and people’s expectations for further autonomy show that the journey toward sustainable peace is complex and requires a strong commitment from all parties concerned.